Costos unitarios y rentabilidad en el carguío, acarreo y conformación de relave filtrado en Setrami, Pataz 2022. - Salvatierra Saavedra, Christian Alberto (2023)
The main objective of the research was to analyze unit costs and valuations to determine the profitability of loading, hauling and shaping filtered tailings in the Setrami mining contract, which is a strategic partner of Compañía Minera Poderosa. The methodology used in the research is of a non-experimental design, descriptive of the application type. The population was made up of the loading, hauling and transportation teams of all the contracts in Poderosa and the sample was made up of the loading, hauling and conformation teams of the Setrami Contract. The data was collected through documentary analysis, likewise to control the data quality, probability was used, being less than 5% with a critical value of 4.26 and an F statistic of 33.76. The results were to analyze the unit costs for the loading, hauling and conformation of filtered tailings, which is 0.38, 2.96 and 0.33 US$/Ton, respectively. The volume of loading, hauling, and shaping of filtered tailings was also valued in the months of June to September 2022, which total valuation is US$143,514.94 for loading, US$163,603.39 for hauling, and US$147,908.25. $ for conformation. In addition, the profitability of the loading, hauling and conformation of filtered tailings was determined in the months of June to September 2022, which the total profitability is 87,697.88 US$ for loading, 43,381.39 US$ for hauling and 99,424.37 US$ for conformation. Finally, it is possible to conclude that the most profitable activity at Setrami is the shaping of filtered tailings and the least profitable is the loading of filtered tailings.